2016
DOI: 10.1093/trstmh/trw057
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of in-hospital mortality and length of stay in community-acquired pneumonia: a 5-year multi-centre case control study of adults in a developing country

Abstract: Several modifiable patient-related and process-of-care factors predicted in-hospital mortality, and length of hospital stay among survivors. Our findings should be used to improve CAP outcomes in developing countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…In fact, Hi was the most common non-pneumococcal pathogen isolate in our study. In the literature, the role of non-pneumococcal pathogens is described as an independent predictor of mortality [29]. Our study described that non-pneumococcal infections were significantly correlated with severe pneumonia possibly because those patients had also compromised a general condition, were undernourished, and had more comorbidities.…”
Section: Discussionmentioning
confidence: 66%
“…In fact, Hi was the most common non-pneumococcal pathogen isolate in our study. In the literature, the role of non-pneumococcal pathogens is described as an independent predictor of mortality [29]. Our study described that non-pneumococcal infections were significantly correlated with severe pneumonia possibly because those patients had also compromised a general condition, were undernourished, and had more comorbidities.…”
Section: Discussionmentioning
confidence: 66%
“… Hedlund et al [ 20 ] 2002 Retrospective Cohort Sweden 17 hospitals 982 5 Outcome Seven university hospitals, 10 county hospitals. The mean PSI varied between 0.9 and 1.9 at different sites Iroezindu et al [ 21 ] 2016 Prospective Case control Nigeria 4 hospitals 400 6 Outcome Not reported All tertiary hospitals Not reported Klausen et al [ 31 ] 2012 Retrospective Analysis of Administrative data Denmark 22 hospitals 11,322 8.5 Outcome Not reported All Danish public health hospitals Not reported Laing et al [ 22 ] 2004 Prospective Cohort New Zealand 2 hospitals 474 7 Both Similar demographics between the two populations except significant differences in ethnicity and rates of COPD. “Similar institutions” No significant differences in disease severity by PSI.…”
Section: Resultsmentioning
confidence: 99%
“…Studies differed in design: seventeen were cohort studies (nine retrospective, seven prospective and one mixed), three were analyses of administrative data, [ 11 , 23 , 31 ] one was a case control study [ 21 ] and one study analysed the baseline population from a randomised control trial [ 29 ]. The median number of units compared across studies was five (IQR 4–15) with a median of 1022 (IQR 445–2009) cases of CAP.…”
Section: Resultsmentioning
confidence: 99%
“…The first is the importance of time to initiation/administration of antibiotics relative to the time of presentation with CAP. Although there has been the odd study suggesting that time to initiation of antibiotics has no impact on various patient outcomes 42 , this contention is not supported by the majority of additional studies 25 , 26 , 43 , 44 . All of the studies from the CAPUCI II Consortium of critically ill patients with CAP indicated that early antibiotic administration (<3 hours) was independently associated with a lower ICU mortality 25 , 26 , 43 .…”
Section: Antibiotic Treatment Of Community-acquired Pneumoniamentioning
confidence: 97%
“…All of the studies from the CAPUCI II Consortium of critically ill patients with CAP indicated that early antibiotic administration (<3 hours) was independently associated with a lower ICU mortality 25 , 26 , 43 . An additional study of hospitalized patients with CAP indicated that delay of the first dose of antibiotics beyond 4 hours was one of the independent predictors of mortality (adjusted OR 3.9) 44 . Furthermore, the systematic review by Lee et al 34 , assessing three aspects of antibiotic therapy in hospitalized patients with CAP, noted that administration of antibiotics within 4 to 8 hours of hospital arrival was associated with a reduction in mortality, although the quality of evidence was assessed as being relatively poor.…”
Section: Antibiotic Treatment Of Community-acquired Pneumoniamentioning
confidence: 99%